Analysis of the price fluctuation of bulk honey (Veterinary Science, 2017)
This work approaches the study of the fluctuations on time series of prices obtained by producers and honey in bulk exporters. It tries to explain the seasonal behavior of price and its implications on the enterprise decision making. It is used as an analisis methodology of the multiplicative model of decomposition
Keywords: Bulk honey prices; Time series